Childhood mycosis fungoides: a report of 20 cases from Turkey. (19th December 2011) - Yazganoglu, K.D.; Topkarci, Z.; Buyukbabani, N.; Baykal, C.
Abstract Background Mycosis fungoides (MF) is the most common type of cutaneous T‐cell lymphomas in adults. In the recent past, several reports have focused on an increased prevalence of MF in children. Objective The present study was aimed to evaluate the clinical characteristics, treatment modalities and disease progression in childhood MF patients from Turkey. Methods In a retrospective analysis of 368 MF patients in a referral center at Istanbul, Turkey, 20 patients were diagnosed before the age of 18 years and were included in the study. Results Childhood cases constituted 5.4% of all MF patients. The age at the time of diagnosis ranged between 2–18 years with a mean of 9.20 ± 4.52 and a median value of 9.50 years. The clinical presentation of MF consisted of solely patches in 60%, followed by plaques or plaques and patches in 40% of the patients. Hypopigmented lesions were seen in 45% and purpuric lesions in 30% of the patients. Four patients (20%) were diagnosed to have unilesional MF. The large majority of the patients (95%) had T1N0M0 or T2N0M0 disease. Sixteen patients were followed between 1–13 years (median: 3.75 years). All the patients were treated with skin directed treatments including topical corticosteroids, topical bexarotene, topical carmustine, narrow band UVB and PUVA. None of the patients progressed to an advanced stage. After an initial clearance, 69.2% of the patients were observed to have recurrences. Conclusion In our experience, patches were more prevalent among childhood MF cases. Overrepresentation of hypopigmented and purpuric lesions was remarkable. Progression to an advanced stage was not seen. However, recurrences after discontinuation of therapy were common.